ANALISIS SEMIOTIKA LAGU-LAGU SUPORTER PERSEBAYA BONEK MANIA - Setyadi, Anugerah; Sudaryanto, Edy; Novaria, Rachmawati (representamen, 2015)
Frenetic football competition in Indonesia led to a phenomenon that exceeds the fame ofcompetition itself , the existence of Supporters at the stadium raises the attractiveness and uniquenessfootball competition in Indonesia . Football supporters in Indonesia arguably is the main attraction ofthe competition. Inside the stadium supporters such doings into separate entertainment for footballlovers nationwide . Large groups of supporters in Indonesia appears to creativities different , rangingfrom Viking or Bobotoh Persib Bandung team supporters group , The Jak Mania , supporters teamPersija Jakarta , Aremania , Arema Malang supporter group , and Bonek Mania , nickname forPersebaya team supporters . Especially for Bonek Mania , this group of supporters often synonymousby the Media and Society with violent , brutal and can not be set , but behind it all was Bonek Maniahas tremendous creativity . Obviously still remembered phenomenal song that was sung Iwak dentgroup Trio Macan , turns the song Iwak dent is Bonek sing songs while supporting Persebaya lyricsare simple was able to attract many people to sing Iwak tiger trio created Bonek dent , researchers feelattracted by the uniqueness of the song is actually what makes the fans make a song for the teamsupported . Surely there is a meaning contained in songs Bonek that, in this study the meaning of thesong will try to be studied more deeply.Keywords : Supporters , songs, Bonek Mania , meaning